Reparation for victims of child pornography under Malaysian Law: An overview - Asril Amirul, Zakariah; Aminuddin, Mustaffa; Nazli Ismail, Nawang; Mohd Badrol, Awang; Mohd Lotpi, Mohd Yusob (2018)
Child pornography is a global issue that has attracted a vast discussion from various parties, including legal scholars. The rapid development of advanced technology and internet has undoubtedly contributed to the prevalence of child pornography over the past twenty-five years. The use of children as subjects of pornographic materials causes devastating and harmful effects on the child victims. The victims of child pornography have suffered from physical, emotional and psychological injury. This paper highlights the significance of material reparations of victims of child pornography. It will also examine current position of Malaysian law on reparation for victims of child pornography. The paper will attempt to identify the shortcomings of existing avenues for redress under the current law and accordingly proposes possible suggestions to address this issue.